1991
DOI: 10.1002/gea.3340060402
|View full text |Cite
|
Sign up to set email alerts
|

Trace‐element variability of native copper within a large ore body: The Kingston mine, Michigan, USA

Abstract: This study attempts both single‐site and regional trace‐element variability assessments focusing on the Kingston Mine, Keweenaw County, Michigan, USA, and other sources of native copper in the Lake Superior region of the United States and Canada. This information is of potential significance to all studies trying to characterize and distinguish between individual mineral sources. It is of particular importance to geoarchaeologists/archaeometrists who are attempting to assign geologic/geographic origin to prehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…To assess inter-source variability, trace element data for four separate copper bearing locales (Kingston, Isle Royale, Michipicoten Island, and Minong) in the Lake Superior area were compared. Through the use of descriptive statistics and analyses of variance on an element-by-element basis, they concluded that regional resource discrimination is unequivocally possible since many more trace elements vary significantly across the Lake Superior district than within Kingston mine [2]. Each of the four Lake Superior sources of native copper thus possesses unique trace element fingerprints or signatures.…”
Section: Methodological Considerationsmentioning
confidence: 97%
See 3 more Smart Citations
“…To assess inter-source variability, trace element data for four separate copper bearing locales (Kingston, Isle Royale, Michipicoten Island, and Minong) in the Lake Superior area were compared. Through the use of descriptive statistics and analyses of variance on an element-by-element basis, they concluded that regional resource discrimination is unequivocally possible since many more trace elements vary significantly across the Lake Superior district than within Kingston mine [2]. Each of the four Lake Superior sources of native copper thus possesses unique trace element fingerprints or signatures.…”
Section: Methodological Considerationsmentioning
confidence: 97%
“…Having demonstrated that there was limited evidence for vertical and horizontal trace element heterogeneity, Allert et al [2] investigated whether variability within the Kingston mine was greater than that across other sources. To assess inter-source variability, trace element data for four separate copper bearing locales (Kingston, Isle Royale, Michipicoten Island, and Minong) in the Lake Superior area were compared.…”
Section: Methodological Considerationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The location of the samples within each source is also an important factor to consider. Of the seven sources, only the Kingston Mine was systematically sampled throughout the portions of the ore body exposed in the mine workings (Allert et al, 1991). The other sources were sampled based on material availability from various institutions and individuals (Rapp et al, 2000: 3, 35-36).…”
Section: Methodsmentioning
confidence: 99%